Volume 7: 2nd Biennial International Conference on Dynamics for Design; 26th International Conference on Design Theory and Meth 2014
DOI: 10.1115/detc2014-35597
|View full text |Cite
|
Sign up to set email alerts
|

Set-Based Thinking in the Engineering Design Community and Beyond

Abstract: Since a series of academic case studies had revealed Toyota’s unique product development practices to the world, a flurry of research has been conducted into set-based design, also known as set-based concurrent engineering. In this paper, we review work related to set-based design across academic communities in efforts to find common themes and influences. After a review of this literature, we inductively arrive at two Principles of Set-Based Thinking: considering sets of distinct alternatives concurrently and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…Other researchers have found similar steps or characteristics of SBD [15,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], but a recent SBD literature search concluded that the literature lacked quantitative, reproducible methods to define, evaluate, and select sets [47]. Specking et al [47] identified an opportunity to develop techniques for SBD trade-off analysis during early design.…”
Section: Set-based Designmentioning
confidence: 82%
“…Other researchers have found similar steps or characteristics of SBD [15,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], but a recent SBD literature search concluded that the literature lacked quantitative, reproducible methods to define, evaluate, and select sets [47]. Specking et al [47] identified an opportunity to develop techniques for SBD trade-off analysis during early design.…”
Section: Set-based Designmentioning
confidence: 82%
“…From this set, we identified and collected only refereed journal articles and conference papers, reducing the set to the 64 SBD specific documents considered in the final review. We refer to this set of documents as Group A throughout the remainder of this paper 2–65 . We provide the complete listing for all Group A documents in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Less common is research combining multiple analytical disciplines within a single SBD construct to develop a holistic methodology describing a quantitative SBD process from the initial early design development and analysis phases to final design selection. Although other researchers have published surveys regarding specific SBD applications or methodologies, none provide a holistic view of SBD methodologies and research trends for complex system design 4,16,17 . We survey and analyze the system‐engineering literature to identify SBD's state‐of‐practice, research trends, and emerging research areas to enable future complex system research and development programs.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it is the time and effort spent handling, exploring and documenting multiple alternatives long into the development process that makes SBCE different. Four of the 24 publications in category 5 simply discuss this vision and practice during the PD process (Liker et al 1996;Al-Ashaab et al 2013, 2016Ghosh & Seering 2014).…”
Section: Classification By Design Process/methodsmentioning
confidence: 99%
“…By aggressively eliminating weak options early in the PDP and thereby confidently concentrating on robust areas that can guarantee flexibility, discovery and innovation, set-based approaches to design make strategic prototype planning/execution a key factor of success in development programmes. Sobek, Ward & Liker (1999) described the three principles of SBCE, which according to Ghosh & Seering (2014) have remained the same as that used for SBCE discussions and implementations across the research and industrial applications.…”
Section: Set-based Designmentioning
confidence: 99%